Absorption laws and reverse order laws for generalized core inverses. Issue 8 (7th July 2021) - Gao, Yuefeng; Chen, Jianlong; Wang, Long; Zou, Honglin
Abstract: In this note, we give necessary and sufficient conditions for which the absorption laws and the reverse order laws of two kinds of generalized core inverses hold.